+0

Differential equation

0
60
1

y''(t) + y(t) = sin(t). Many thanks.

Guest Jun 14, 2017
Sort:

#1
0

Solve ( d^2 y(t))/( dt^2) + y(t) = sin(t):
The general solution will be the sum of the complementary solution and particular solution.
Find the complementary solution by solving ( d^2 y(t))/( dt^2) + y(t) = 0:
Assume a solution will be proportional to e^(λ t) for some constant λ.
Substitute y(t) = e^(λ t) into the differential equation:
( d^2 )/( dt^2)(e^(λ t)) + e^(λ t) = 0
Substitute ( d^2 )/( dt^2)(e^(λ t)) = λ^2 e^(λ t):
λ^2 e^(λ t) + e^(λ t) = 0
Factor out e^(λ t):
(λ^2 + 1) e^(λ t) = 0
Since e^(λ t) !=0 for any finite λ, the zeros must come from the polynomial:
λ^2 + 1 = 0
Solve for λ:
λ = i or λ = -i
The roots λ = ± i give y_1(t) = c_1 e^(i t), y_2(t) = c_2 e^(-i t) as solutions, where c_1 and c_2 are arbitrary constants.
The general solution is the sum of the above solutions:
y(t) = y_1(t) + y_2(t) = c_1 e^(i t) + c_2 e^(-i t)
Apply Euler's identity e^(α + i β) = e^α cos(β) + i e^α sin(β):
y(t) = c_1 (cos(t) + i sin(t)) + c_2 (cos(t) - i sin(t))
Regroup terms:
y(t) = (c_1 + c_2) cos(t) + i (c_1 - c_2) sin(t)
Redefine c_1 + c_2 as c_1 and i (c_1 - c_2) as c_2, since these are arbitrary constants:
y(t) = c_1 cos(t) + c_2 sin(t)
Determine the particular solution to ( d^2 y(t))/( dt^2) + y(t) = sin(t) by the method of undetermined coefficients:
The particular solution to ( d^2 y(t))/( dt^2) + y(t) = sin(t) is of the form:
y_p(t) = t (a_1 cos(t) + a_2 sin(t)), where a_1 cos(t) + a_2 sin(t) was multiplied by t to account for sin(t) in the complementary solution.
Solve for the unknown constants a_1 and a_2:
Compute ( d^2 y_p(t))/( dt^2):
( d^2 y_p(t))/( dt^2) = ( d^2 )/( dt^2)(a_1 t cos(t) + a_2 t sin(t))
= -a_1 t cos(t) - 2 a_1 sin(t) + 2 a_2 cos(t) - a_2 t sin(t)
Substitute the particular solution y_p(t) into the differential equation:
( d^2 y_p(t))/( dt^2) + y_p(t) = sin(t)
-a_1 t cos(t) - 2 a_1 sin(t) + 2 a_2 cos(t) - a_2 t sin(t) + a_1 t cos(t) + a_2 t sin(t) = sin(t)
Simplify:
2 a_2 cos(t) - 2 a_1 sin(t) = sin(t)
Equate the coefficients of cos(t) on both sides of the equation:
2 a_2 = 0
Equate the coefficients of sin(t) on both sides of the equation:
-2 a_1 = 1
Solve the system:
a_1 = -1/2
a_2 = 0
Substitute a_1 and a_2 into y_p(t) = a_2 t sin(t) + a_1 t cos(t):
y_p(t) = -1/2 t cos(t)
The general solution is:
Answer: | y(t) = y_c(t) + y_p(t) = -1/2 t cos(t) + c_1 cos(t) + c_2 sin(t)

Guest Jun 14, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details